PREDIKSI NILAI BATAS ELASTISITAS BAJA KONSTRUKSI DENGAN UJI KEKERASAN BRINELL DAN VICKERS - Vinan Viyus; Khambali (Politeknik Negeri Malang, 2020)
This study aimed to determine the correlation value against the value of hard carbon steel with elasticity it. This is done by determining the formula formulation in the form of the regression equation Y = AX1 + BX2. Data taken from the sample used in the form of a cylindrical rod test specimens and the steel plate. Severity using the Brinell test, whereas withdrawal using tensile testing machine. The results were obtained for cylindrical steel Y = 2,41 X1 – 0,4347X2 and for specimens of steel plate (flat) Y = 2,35 X1 – 0,534X2. Y is the value of the rigidity, and X1 is hardness of steel. While X2 arises from material stretch factor. Probability influence of workmanship and style fluctuate respectively 0,4347 and 0,534 is much larger than 0.05 (a standard which is commonly used). This means that the regression coefficient is not significantly different effect. Decrease in strength may be due to the loss of influence of the stress concentration occurs. In addition it could also be due to the configuration of the carbon forming constituents uneven in areas experiencing strain due to the with drawalprocess